Priority Development Projects of the Arctic Zone. Reconstruction of the Northern Sea Way - F. P. Isaev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article describes Arctic zone and the significance of its resources for the Russian Federation and foreign countries. The basic strategic documents of the Arctic zone are listed. Priority projects for the development of the Arctic zone are considered. The reference zones of development in the Arctic and the influence of their formation on the macro region are analyzed. Areas of the main projects implemented or planned for implementation in the Arctic zone of the Russian Federation in percentage terms are presented. The state program of the Russian Federation «Socio-economic development of the Arctic zone of the Russian Federation», stages of implementation are considered. The main events of the VII International Forum «The Arctic: the present and the future» are revealed. The characteristic of the Northern Sea Route is given, its social and economic efficiency for the Russian Federation and the regions of the North is justified. The Northern Sea Route and the Southern Sea Route are compared. The criteria for increasing the carrying capacity of the Northern Sea Route are given. Areas of funding for improving the infrastructure of the region are indicated. The problem directions of the Northern Sea Route development have been identified: financial support for Northern Sea Route rehabilitation projects, political confrontation and a lack of qualified personnel. The characteristic of professional standards and their benefits for the enterprises of the region is presented. Recommendations are given on involving people in production and in the region.